Detecção molecular e parasitológica de Leishmania spp. em díptero da espécie Tabanus importunus - Coelho, Willian Marinho Dourado [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2013)
Leishmaniasis is an important chronic zoonosis caused by protozoa of the genus Leishmania spp. The major vectors of this protozoosis are sand flies, and Lutzomyia longipalpis is considered the main species implicated in the transmission of American Visceral Leishmaniasis in Brazil. The presence of the parasite's deoxyribonucleic acid (DNA) in ectoparasites such as ticks and fleas has prompted speculations about the existence of new vectors in the cycle of leishmaniasis. The aim of this paper is to report the molecular detection of Leishmania spp. in a horse fly of the species Tabanus importunus which parasitized an oligosymptomatic dog infected with Leishmania spp. Molecular amplification of the protozoan's DNA in the head, thoracic region and abdomen of the tabanid tested positive for Leishmania complex. This is the first report of the presence of DNA from Leishmania spp. in dipterous insects of the species T. importunus.
Molecular and parasitological detection of Leishmania spp. in a dipteran of the species Tabanus importunes
Keywords: Canine visceral leishmaniasis; Dogs; Horse fly; PCR; Protozoan; Vectors